PENGARUH MOTIVASI TERHADAP KUALITAS PELAYANAN PADA UNIT LAYANAN PENGADAAN KABUPATEN MAMUJU UTARA - Talle, Ambo (Katalogis, 2016)
This study aims to determine the level of motivation influence on the quality of service on the Procurement Services Unit Mamuju Utara.Jenis quantitative research with survey approach. This study population Procurement Services Unit employees and partners in the Procurement Services Unit of North Mamuju regency are 54 people consisting of 14 members, Procurement Unit and the 40 partners that are determined by census so that the total sample of 54 respondents. Data collection techniques including observation, questionnaire, and documentation, while data analysis techniques using simple linear regression.The results showed the influence of motivation on the quality of service at the Procurement Unit of North Mamuju regency is determined by physiological needs, safety needs, social needs, esteem needs and the needs of the influence diri.Besar actualization of 63.3% to the level of relations "strong". Descriptive analysis shows the dimensions of self-actualization needs had the highest percentage, in terms of implementation of tasks and employees have the skills means that employees Procurement Services Unit is able to do a good job and they have the skills to do the job, while the dimensions of the lower is the need for security in case of a guarantee health and safety working conditions, which means that employees of the Procurement Services Unit of North Mamuju regency lack health insurance and they feel less safe to do work in his office room.